Oviposition behavior is not affected by ultraviolet light in a butterfly with sexually‐dimorphic expression of a UV‐sensitive opsin - Jose Borrero; Daniel Shane Wright; Caroline Nicole Bacquet; Richard M. Merrill (Ecology and Evolution)
Abstract Animal vision is important for mediating multiple complex behaviors. In Heliconius butterflies, vision guides fundamental behaviors such as oviposition, foraging, and mate choice. Color vision in Heliconius involves ultraviolet (UV), blue and long‐wavelength‐sensitive photoreceptors (opsins). Additionally, Heliconius possess a duplicated UV opsin, and its expression varies widely within the genus. In Heliconius erato, opsin expression is sexually dimorphic; only females express both UV‐sensitive opsins, enabling UV wavelength discrimination. However, the selective pressures responsible for sex‐specific differences in opsin expression and visual perception remain unresolved. Female Heliconius invest heavily in finding suitable hostplants for oviposition, a behavior heavily dependent on visual cues. Here, we tested the hypothesis that UV vision is important for oviposition in H. erato and Heliconius himera females by manipulating the availability of UV in behavioral experiments under natural conditions. Our results indicate that UV does not influence the number of oviposition attempts or eggs laid, and the hostplant, Passiflora punctata, does not reflect UV wavelengths. Models of H. erato female vision suggest only minimal stimulation of the UV opsins. Overall, these findings suggest that UV wavelengths do not directly affect the ability of Heliconius females to find suitable oviposition sites. Alternatively, UV discrimination could be used in the context of foraging or mate choice, but this remains to be tested.